Leashing the dogs of war : conflict management in a divided world - Crocker, Chester A.; Hampson, Fen Osler; Aall, Pamela R. (Washington, D.C. : United States Institute of Peace Press, 2007)
"Recognizing the significance of changes in the international relations climate, the editors developed this volume to present new perspectives on how best to prevent, manage, or resolve conflicts. Together with forty of the most influential and innovative analysts of international affairs, they provide the latest thinking, practice and research in the field of international relations and conflict resolution". --Publisher.
Leashing the dogs of war / Chester A. Crocker, Fen Osler Hampson, and Pamela Aall -- Sources of conflict and challenges to global security -- International sources of interstate and intrastate war / Jack S. Levy -- New global dangers / Michael E. Brown -- Arms acquisition and violence : are weapons or people the cause of conflict? / Geoffrey Kemp -- Terrorism and global security / Martha Crenshaw -- The challenge of weak, failing and collapsed states / Robert I. Rotberg -- State making, state breaking, and state failure / Mohammed Ayoob -- Power, social violence, and civil wars / Charles King -- Minorities, nationalists, and islamists : managing communal conflict in the twenty-first century / Ted Robert Gurr -- Turbulent transitions : why emerging democracies go to war / Edward D. Mansfield and Jack Snyder -- Environmental change, security, and conflict / Nils Petter Gleditsch -- Economic causes of civil conflict and their implications for policy / Paul Collier -- Economic causes of conflict : an overview and some policy implications / Frances Stewart and Graham Brown -- Uses and limits of force in conflict management -- Using force for peace in the age of terror / Lawrence Freedman -- Limits on the use of force / Brian Urquhart -- Yet again : humanitarian intervention and the challenges of "never again" / Bruce W. Jentleson -- Coercive diplomacy, Robert J. Art and Patrick M. Cronin -- Expanding global military capacity to save lives with force / Michael O'Hanlon -- Economic sanctions international peace and security / Chantal de Jonge Oudraat -- Uses and limits of statecraft, diplomacy and soft power in conflict management -- The place of grand strategy, statecraft and power in conflict management / Chester A. Crocker -- Usip framework for success in international intervention / Daniel Serwer and Patricia Thomson -- The place of soft power in state-based conflict management / Joseph S. Nye, jr -- Rule of law in conflict management / Neil Kritz -- Rethinking the "war on terror" : new approaches to conflict prevention and management in the post-9/11 world / Paul B. Stares and Mona Yocoubian -- International mediation / I. William Zartman and Saadia Touval -- Contemporary conflict resolution applications / Louis Kriesberg -- The power of non-official actors in conflict management / Pamela Aall -- Uses and limits of institutions in conflict management -- An institutional architecture for peace / Brian Job -- The United Nations and conflict management : relevant or irrelevant? / Karen A. Mingst and Margaret P. Karns -- Successes and challenges in conflict management / Andrew Mack -- New roles for regional organizations / Paul F. Diehl -- Capacity and limits of NGOs as conflict managers / Diana Chigas -- The role of norms, standards, and regimes / Ruth Wedgwood -- The uses and limits of governance in conflict management -- The challenges of imposed democracy / Marina Ottaway -- Peace enforcement or liberal imperialism? / Kimberly Marten -- Economic factors in civil wars : policy considerations / David Malone and Jake Sherman -- Sharing sovereignty : new institutions for collapsed and failing states / Stephen Krasner -- Intervention and the nation-building debate / Fen Osler Hampson and David Mendeloff.
Includes bibliographical references and index.
Keywords: Peaceful change (International relations); Conflict management; Security, International; Conflict management; Peaceful change (International relations); Security, International; Peaceful change (International relations); Conflict management; Security, International